COMPLEMENTARITY BETWEEN EPSILON AND PHI SEQUENCES IN PREGENOMIC RNA INFLUENCES HEPATITIS B VIRUS REPLICATION EFFICIENCY - Oropeza, Claudia E. (2006)
Hepatitis B virus (HBV) replication requires the viral polymerase to reverse transcribe the 3.5-kb pregenomic viral RNA within the nucleocapsid. It has been proposed that a sequence element designated phi (φ), which is located 32 nucleotides upstream of the 3′ DR1 pregenomic RNA sequence and is complementary to ε, is required for efficient minus-strand synthesis because it may mediate the translocation of the viral polymerase plus the three nucleotide primer from ε to DR1. A mutation in φ has been identified which can be compensated for with a complementary mutation in ε. This observation supports the suggestion that ε and φ base pair during the process of polymerase translocation from ε to DR1. However, additional mutations in φ were not complemented by the corresponding mutations in ε indicating that the functional recognition of ε and ε/φ stem-loop structures by polymerase probably requires both sequence- and structure-specific information.